Assessment of Readability Risks in Contracts Causing Conflicts in Construction Projects - Koc, Kerim; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2021)
Readability and comprehensibility of contracts are important. A contract would be more practical and functional if the clauses can be interpreted more consistently. Therefore, an analysis of risks influencing readability of construction contracts other than the more common approach of analyzing operational risk is essential. This paper aims to assess risk factors affecting readability of contracts to avoid or minimize conflicts among project parties by adopting a fuzzy Visekriterijumska Optimizacija I Kompromisno Resenje (VIKOR) technique. Readability risks were analyzed based on conflicting potential interpretations of clauses on time, cost, and quality criteria. The results identified the top three risks as: (1) unnecessary complexity in using nouns and improper use of referents; (2) the use of abstract and ambiguous words or sentences leading to multiple interpretations; and (3) unnecessarily long sentence length. To establish consensus among experts, compare stakeholders' perceptions, and ensure the robustness of the model, interrater agreement (IRA) analysis, Mann-Whitney U test, and sensitivity analysis were performed. The findings can help contract drafters recognize the importance of the role of readability of contracts. Improved readability can potentially lead to reduced conflicts, claims, and disputes in construction projects. (C) 2021 American Society of Civil Engineers.
Keywords: Conflict prevention; Construction contract; Contract interpretation; Contractual risk; Fuzzy VIKOR; Readability; DECISION-MAKING APPROACH; EXTENDED VIKOR METHOD; LOCATION SELECTION; AHP; MANAGEMENT; MODEL; PERSPECTIVE; ENVIRONMENT; FACILITY; Construction & Building Technology; Engineering